2004
DOI: 10.1080/09637480400015745
|View full text |Cite
|
Sign up to set email alerts
|

The status of wild food plants in Bulamogi County, Uganda

Abstract: We present here an inventory of the edible plants of Bulamogi, Uganda, and related aspects of exploitation of wild food plants (WFPs) by the local community. The edible plants consist of 105 species distributed in 77 genera and 39 families. Most of the edible plants are herbaceous (70.7%) and are cultivated (49.1%). Some introduced food plants have become naturalised and grow wild. Most of the edible plants yield fruits that are consumed as snacks (41.4%). The major food crops of the Balamogi are consumed loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 9 publications
5
41
1
Order By: Relevance
“…The present study concurs with previous studies which revealed that educated Kenyans, South Africans and Ugandans who earn more than the less educated, viewed traditional and indigenous foods as food for the poor; hence having less preference to consume traditional and indigenous African foods as compared to the western processed foods (Tabuti et al, 2004;Kimiywe et al, 2007;Dweba and Mearns, 2011). In comparison with the consumption levels, of the uneducated in Kenya, South Africa and Uganda, educated populations have been found to consume less of wild and indigenous fruits and vegetables (Oniang'o et al, 2003;Pelto et al, 2004;Tabuti et al, 2004). The educated Kenyans, South Africans and Ugandans are exposed to influences of urbanisation and western lifestyles, which lead to adopting negative perceptions towards local and indigenous African foods (Haddad, 2003;Pingali, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The present study concurs with previous studies which revealed that educated Kenyans, South Africans and Ugandans who earn more than the less educated, viewed traditional and indigenous foods as food for the poor; hence having less preference to consume traditional and indigenous African foods as compared to the western processed foods (Tabuti et al, 2004;Kimiywe et al, 2007;Dweba and Mearns, 2011). In comparison with the consumption levels, of the uneducated in Kenya, South Africa and Uganda, educated populations have been found to consume less of wild and indigenous fruits and vegetables (Oniang'o et al, 2003;Pelto et al, 2004;Tabuti et al, 2004). The educated Kenyans, South Africans and Ugandans are exposed to influences of urbanisation and western lifestyles, which lead to adopting negative perceptions towards local and indigenous African foods (Haddad, 2003;Pingali, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…We used a familiarity index (FI) as a relative indicator of the popularity of the wild and semi-wild fruits within the communities (Tabuti et al 2004), which was computed using:…”
Section: Discussionmentioning
confidence: 99%
“…Wild and semi-wild fruit resources are not only important as food but may also have several other functions and services (Motlhanka et al 2008, Tabuti et al 2004, such as medicinal applications or bee forage, although their relative importance depends on local circumstances. Due to their diverse functions, these resources may be exposed to overexploitation or otherwise threatened, especially in periods of food scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…This ecological degradation eliminated many indigenous food trees and gathered foods from the diet 64 . Several indigenous fruit species and wild food plants diminished in the traditional diets, affecting the taste and nutrient content of common dishes 43,65,66 .…”
Section: Ecological Destructionmentioning
confidence: 99%
“…These methods of 'education' have uniformly reduced knowledge related to the cultivation and preparation of traditional and wild foods 76 . Traditional knowledge has been devalued as the education of children has shifted away from the tribal elders, the primary educators in the past, to the imperial powers via the church and school 64,77 . 'Education' encouraged 'sophistication', which included a repugnance for traditional foods and ancient methods of food preparation 76 , explaining, at least partially, why nutritious, indigenous foods are drastically underutilised and undervalued today 66,[78][79][80][81] .…”
Section: Loss Of Indigenous Marketsmentioning
confidence: 99%